Energy abundance, trade and industry location - Reyer Gerlagh; Nicole A. Mathys (Fondazione Eni Enrico Mattei (FEEM), 2011)
We study the effect of countries' energy abundance on trade and sector activity, conditional on sector's energy intensity, using an unbalanced panel with 14 high-income countries from Europe, America and Asia, 10 broad sectors, and years 1970-1997. We find that (i) countries with large energy endowments have low energy prices, and are thus energy abundant both on micro and macro level. (ii) Energy abundant countries have a high level of energy embodied in exports relative to imports. (iii) Energy intensive sectors export from and (iv) have higher economic activity in energy abundant countries. (v) The trade and location effects increase with a sector's exposure to international trade. In short, energy is a major driver for sector location through specialisation. We show that capital and energy are complements in the production function and use various controls in our analysis. The results give insights into delocalisation effects that may take place among rich countries with heterogeneous energy policy.
Keywords: Q56; 330; Trade and the Environment; Pollution Haven; Factor Endowments; Industry Location